Iron deficiency and childhool morbidity - A. H. Markum; C. Windrajati Marwoto; Maria Abdulsalam; D. Gatot; I. Wahidayat; S. Muslichan (Indonesian Pediatric Society, 1981)
Although it is likely that individual iron status will influence infections, results of various studies on immune response in iron deficient children remain controversial. This situation is becoming more complicated if projected in clinical field trials where multi and interrelated factors contribute to the occurrence of infection as commonly found in developing countries.Our results in this field study in semi urban areas which covered 95 children of low and moderate socio-economic families showed that:I. Iron deficient children are more susceptible to infection than normal children.2. The frequency of infection is correlated with the severity of iron deficiency, but not with the hemoglobin level.3. In under-nourished children, however, the frequency of infection depends mainly on the nutritional status rather than on the degree of iron deficiency.